Effects of antipsychotic drugs on neurites relevant to schizophrenia treatment - Huang, Xu‐Feng; Song, Xueqin (Medicinal research reviews, 2019)
Although antipsychotic drugs are mainly used for treating schizophrenia, they are widely used for treating various psychiatric diseases in adults, the elderly, adolescents and even children. Today, about 1.2% of the worldwide population suffers from psychosis and related disorders, which translates to about 7.5 million subjects potentially targeted by antipsychotic drugs. Neurites project from the cell body of neurons and connect neurons to each other to form neural networks. Deficits in neurite outgrowth and integrity are implicated in psychiatric diseases including schizophrenia. Neurite deficits contribute to altered brain development, neural networking and connectivity as well as symptoms including psychosis and altered cognitive function. This review revealed that (1) antipsychotic drugs could have profound effects on neurites, synaptic spines and synapse, by which they may influence and regulate neural networking and plasticity; (2) antipsychotic drugs target not only neurotransmitter receptors but also intracellular signaling molecules regulating the signaling pathways responsible for neurite outgrowth and maintenance; (3) high doses and chronic administration of antipsychotic drugs may cause some loss of neurites, synaptic spines, or synapsis in the cortical structures. In addition, confounding effects causing neurite deficits may include elevated inflammatory cytokines and antipsychotic drug‐induced metabolic side effects in patients on chronic antipsychotic therapy. Unraveling how antipsychotic drugs affect neurites and neural connectivity is essential for improving therapeutic outcomes and preventing aversive effects for patients on antipsychotic drug treatment.